Performances of air plasma sprayed thermal barrier coatings for industrial gas turbines - Seraffon, Maud (Cranfield University, 2012)
Future industrial gas turbines will be required to operate at higher temperatures to increase operating efficiencies and will be subjected to more frequent thermal cycles. The temperatures that the substrates of components exposed in the harshest environments experience can be reduced using air-cooling systems coupled with ceramic thermal barrier coatings (TBCs); however, few studies have been carried out at the substrate temperatures encountered in industrial gas turbines (e.g. 900 – 1000 °C). Better understanding of their behaviour during service and, their various potential failure mechanisms, would allow more accurate prediction of TBC lifetimes and improve coatings. The aim of this research, as a part of the Supergen Plant Life Extension (PLE) project, was (a) to investigate the influence of industrial gas turbine blade geometry on TBC system lifetimes, and (b) to extend knowledge on the effect of bond coat composition on the oxide growth at temperatures below 1000 °C. The main results of this thesis, obtained using mass change and characterisation techniques, increase the understanding of the significant interactions between the different coating layers, samples’ geometry, interdiffusion and failure mechanisms involved during oxidation. Curvature was found to affect the quality of manufacture and thus promoted premature failure at the convex features of modified aerofoil-shaped samples. In parallel new bond coat compositions, suitable for industrial gas turbines were suggested from the wide range investigated in oxidation exposures. The selective growth of protective Cr2O3 or Al2O3 oxides or other mixed oxides was observed and mapped in ternary diagrams. Furthermore two novel techniques were successfully used during this project. Pulsed flash thermography proved to be efficient in identifying areas of sub-surface TBC delamination non-destructively. Magnetron co-sputtering using 2 and 3 targets was found to be a flexible method to deposit thick coatings with a wide range of compositions.